The Relationship Between Perceived Health Needs and Perceived Benefits of Participating in the JKN Program in Kedungwuni District in 2026 - Salsabilla Ramadhani; Yuniarti Yuniarti; Teguh Irawan (Program Studi Sarjana Kesehatan Masyarakat Universitas Prima Indonesia, 2026)
The National Health Insurance (JKN) program aims to improve access to healthcare services and provide financial protection for the Indonesian population. Despite the increasing coverage of JKN enrollment, public perceptions of its benefits remain varied. This study aimed to analyze the relationship between perceived health needs and the perceived benefits of participating in the JKN program among residents of Kedungwuni District, Pekalongan Regency, in 2026. A quantitative study with a cross-sectional design was conducted involving 100 respondents selected through purposive sampling. Perceived health needs, operationalized through perceived susceptibility and perceived severity based on the Health Belief Model, served as the independent variable, while perceived benefits of JKN participation were the dependent variable. Data were collected using a Likert-scale questionnaire and analyzed through univariate analysis and the Chi-Square test. The results showed that 51.0% of respondents had high perceived health needs, while 55.0% had positive perceptions of JKN benefits. A significant relationship was found between perceived health needs and perceived benefits of participating in the JKN program (p=0.000), with a Contingency Coefficient of 0.339 indicating a moderate association. Higher perceived health needs were associated with more positive perceptions of JKN benefits.